Kepuasan Pasien terhadap Mutu Layanan di Puskesmas Banjarbaru Selatan - Rahman, Eddy; Mahmudah, Mahmudah; Rahmi, Khalifatur (Jurnal Akademika Baiturrahim Jambi, 2025)
Patient dissatisfaction can be caused by various things, including inefficient time, poor product or service quality, service quality, prices or costs that do not meet patient expectations. Factors causing patient dissatisfaction include the quality of health services that are below standard. Service satisfaction standards are set nationally according to the Minister of Health of the Republic of Indonesia in 2016 concerning Minimum Service Standards for patient satisfaction, namely above 95%. The aim of this research is to identify and analyze the relationship between the quality of health services and patient satisfaction at the South Banjarbaru Community Health Center. This research method is quantitative research with a cross sectional design approach. The population in this study was an average of 1398 patients seeking treatment at Puskesmas Banjarbaru Selatan  2022. The sampling method was 94 respondents using accidental sampling and tested using Chi-Square analysis. Univariate results of patient satisfaction 89.4% satisfied, reliability 84.0% good, responsiveness 92.6% good, assurance 90.4% good, empathy 97.9% good and tangible 88.3% good. The results of this analysis bivariat show that between 5 dimensions of health service quality with patient satisfaction at Puskesmas Banjarbaru Selatan, namely reliability (p-value = 0.000) OR (95% CI) = 22.167 (4.770-103.009), responsiveness (p-value 0.025) OR (95% CI) = 8.571 (1.590-46.199), empathy (p-value=0.010) OR (95% CI) =0,887 (0,043-0,169), tangible (p-value 0.015) OR (95% CI)=7.333 (1.664-32.312) there is a relationship with patient satisfaction at Puskesmas Banjarbaru Selatan, while assurance (p-value=0.052) OR (95% CI) =5.571 (1.140-27.241) has no relationship to patient satisfaction. It is hoped that the community health center can increase the response speed of services, improve facilities and infrastructure so that public complaints can be minimized and the E-puskesmas system can be utilized optimally